Pengaruh Modal Usaha Non Halal Terhadap Minat Beli Telur pada Pengusaha Ayam Petelur di Desa Karang Semanding - Nur, Dimas; Syarofi, Muhammad (Universitas Sahid Surakarta, 2025)
This research aims to examine the influence of non-halal business capital on interest in buying eggs among the community, especially among laying hen entrepreneurs in Karang Semanding Village, Padukuhan Lor. The method used is a quantitative approach with an explanatory design, where data is collected through questionnaires distributed to respondents. The population in this study consisted of 100 egg consumers, and the sample size was determined using the Slovin formula with an error rate of 5%, resulting in 80 respondents selected using simple random sampling. The research results show that non-halal business capital has a significant influence on consumer buying interest, which is reflected in increased business performance and trust in products. The findings of this research lie in emphasizing that the use of non-halal capital is not always a barrier, as long as the products offered meet the quality standards expected by consumers. It is hoped that this research can contribute to the development of the livestock sector and provide guidance for entrepreneurs in making wiser decisions.